Universities as a Source of Precarious Employment - Anatoly V. Merenkov; Natalya L. Antonova; Evgeny L. Bakhtin; Galina I. Popova (National Research Mordova State University, 2023)
Introduction. Rapid social changes and new challenges are increasingly transforming all spheres of human life. These factors affect not only the labor market and the general nature of professional activities, but also educational approaches to training specialists in the higher education system. Modern university graduates should possess competencies that meet diverse employer expectations. At the same time, universities are becoming "factories" for the production of graduates focused on precarious employment, since the uncertainty in the type of employment caused by global transformations in the labor market is reorienting the higher education system, thereby changing the vector of educational activity. Aim - analysis of studentsʼ orientations towards precarious employment and identification of the role of universities in their development. Materials and Methods. In 2021, an empirical sociological survey was conducted. The survey sample included 716 learners studying at Yekaterinburg universities, who were interviewed using a questionnaire. In order to elucidate the process of forming studentsʼ orientation towards precarious employment and the role of universities therein, we used semi-formalized interviews with young people whose activities in the labor market could be characterized as atypical employment, as well as with heads of educational programs and curators of projectoriented programs at the Ural Federal University. In addition, the results of a study conducted in 2020-2021 among university graduates in the Ural region were used. Results. Uncertainty in the labor market, secondary employment and involvement of university students in project-oriented activities form their following work preferences: the desire for atypical forms of employment, irregular working hours, and free work schedules. Discussion and Conclusion. The conclusions made by the authors expand the understanding of the needs of young people in the labor market and the transformation of university education in conditions of uncertainty. The materials of the article contribute to the development of sociological knowledge and can be useful to management and administrative structures of Russian universities.